Dossier Editorial - Training in Animation Theater: The good winds of Targoviste, Romania (Urdimento: Revista de Estudos em Artes Cênicas, 2018)
This text presents the Union Internationale de la Marionette - UNIMA, an organization founded in 1929 in Prague, (Czechoslovakia). It presents the first International Meeting on Training in the Arts of the Puppetry held in Charleville-Mézières, France, in September 2015. And make the editorial pf the Dossier - Formation to the Animation Theater that publishes exhibitions that took place at the second International Training Meeting in the Arts of the Puppet, that took place in Targoviste, Rumania, in June of 2017.